2023
DOI: 10.1039/d2ee03271f
|View full text |Cite
|
Sign up to set email alerts
|

Directing the research agenda on water and energy technologies with process and economic analysis

Abstract: Climate change is directly impacting energy consumption, water availability, and agricultural production. Among the global efforts to address the root causes of carbon emissions, numerous emerging technologies have been proposed...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 94 publications
0
11
0
Order By: Relevance
“…As a thermally driven membrane-based process, MD involves a phase change. Owing to the continuous water-to-vapor conversion at the feed solution/membrane interface, the driving force gradually decreases due to heat loss, resulting in deteriorated vapor flux and energy inefficiency. , Furthermore, the phenomenon of TP is aggravated along the length of MD module, limiting the scale-up of MD operation. , To alleviate the negative impacts of TP on MD, photothermal membrane distillation (PMD) has been proposed, which combines a surface self-heating membrane with renewable solar energy. In PMD, the modified membrane with photothermal materials can harvest solar energy and generate localized heat on the membrane surface, thus maintaining a high cross-membrane temperature gradient as the driving force. Another obstacle impeding the application of MD lies in membrane fouling and wetting issues when treating contaminated saline solutions.…”
Section: Design and Characterization Of The Hydrogel Composite Pmd Me...mentioning
confidence: 99%
“…As a thermally driven membrane-based process, MD involves a phase change. Owing to the continuous water-to-vapor conversion at the feed solution/membrane interface, the driving force gradually decreases due to heat loss, resulting in deteriorated vapor flux and energy inefficiency. , Furthermore, the phenomenon of TP is aggravated along the length of MD module, limiting the scale-up of MD operation. , To alleviate the negative impacts of TP on MD, photothermal membrane distillation (PMD) has been proposed, which combines a surface self-heating membrane with renewable solar energy. In PMD, the modified membrane with photothermal materials can harvest solar energy and generate localized heat on the membrane surface, thus maintaining a high cross-membrane temperature gradient as the driving force. Another obstacle impeding the application of MD lies in membrane fouling and wetting issues when treating contaminated saline solutions.…”
Section: Design and Characterization Of The Hydrogel Composite Pmd Me...mentioning
confidence: 99%
“…Proton exchange membrane and alkaline water splitting powered by renewable energy are attractive methods for H 2 production [ 5 ]. Economically, the cost of proton exchange membrane and alkaline water electrolysis is less than the cost of direct seawater electrolysis per cubic meter [ 6 ]. However, pure water shortage has become a serious issue hindering the large-scale application of the above technology [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…29 Although previous analysis has confirmed that the specific energy consumption of seawater purification costs only a small fraction of the overall cost of hydrogen production (0.05-0.14%), given that water electrolysis is an energyintensive process and that its future requirements will be on a large scale, any energy-saving measures will provide substantial economic benefits. 30 Over the past few years, researchers have attempted to overcome the challenges associated with DSE and TSSE. 31,32 Recently, integrating seawater purification and electro-splitting into a single system (named as ISPE technology) has emerged as a highly advanced and promising alternative to DSE and TSSE (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…29 Although previous analysis has confirmed that the specific energy consumption of seawater purification costs only a small fraction of the overall cost of hydrogen production (0.05–0.14%), given that water electrolysis is an energy-intensive process and that its future requirements will be on a large scale, any energy-saving measures will provide substantial economic benefits. 30…”
Section: Introductionmentioning
confidence: 99%